X-ray fluorescence (Ti/Ca and Zr/Rb ratios) in sediment core MD99-2198 (0-125 ka) - Anastasia Zhuravleva (PANGAEA, 2021)
X-ray fluorescence data (Ti/Ca and Zr/Rb ratios) were obtained using the Aavatech XRF Core Scanner at University Kiel in two runs (10 kv, 750 mA, 10 seconds and 30 kv, 2000 mA, 20 seconds). Elemental intensities were measured every 1 cm between 0-18.83 m and 0.5 cm between 18.84-22 m (revised depth). Note that the original core depth scale in core MD99-2198 was modified by excluding two intervals (10.06-10.24 m and 13.78-14.30 m), representing episodes where the core was ripped apart, as could be concluded on the basis of large increases in porosity.